Penerapan Kegiatan Finger Painting Menggunakan Bahan Alam Untuk Mengembangkan Kreativitas Anak Usia 4-5 Tahun - Dede Homsanah; Siti Kholifah; Ratu Yustika Rini; Nuryati Nuryati (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This research was motivated by the low creativity levels of 4–5-year-old children at PAUD Al-Muttaqin, influenced by limited creative stimulation and excessive gadget use. Children’s creativity needs to be fostered through exploratory activities, one of which is natural-material-based finger painting that is safe and environmentally friendly. This study aims to describe the implementation of finger painting using natural materials and to examine its effects on early childhood creativity development. A descriptive qualitative method was employed, with data collected through observation, interviews, and documentation. The research subjects consisted of eight children aged 4–5 years and one classroom teacher. The findings reveal that finger painting with natural materials significantly enhanced children’s creativity. Six children who initially showed creative tendencies demonstrated improvement in color combination skills, imaginative drawing, and independent expression. Two initially passive children gradually developed the ability to explore colors and forms and articulate their creative processes. Natural materials provided strong sensory stimulation that increased children’s interest, expressive confidence, and fine motor coordination. Overall, natural-material-based finger painting proved effective as a creative stimulation method in early childhood education